Content of university alcohol policies in New South Wales, Australia. (12th October 2018) - Chitty, Kate M.; Chow Chuen, Johanna A. P.; Howse, Eloise; Thow, Anne Marie
Abstract: Issue addressed: This study aimed to develop a working checklist for university alcohol policies and apply this checklist to current policies in universities in New South Wales (NSW), Australia. Methods: We developed a working checklist of possible university alcohol policy approaches, drawn from the World Health Organization's alcohol policy recommendations, university alcohol policy research from the United States and norms and expectations currently incorporated in Australian university alcohol policies. We then conducted a content analysis of university alcohol policies in NSW, Australia, based on this checklist. All NSW university websites were searched for any policies or guidelines related to alcohol. The content of each policy or guideline was assessed in terms of whether it satisfied the various components of the checklist. Results: All 11 universities in NSW have an alcohol policy, and these policies are readily available and accessible online. There were two main themes identified in the aims across documents: maximising health and safety of individuals and protecting the university as an institutional entity. Inclusiveness and safety were the predominant themes that satisfied policy content. No document incorporated methods for monitoring/evaluating policy impact. Conclusions: University alcohol policies that incorporated both individual‐level and population‐based approaches to alcohol harm reduction were more likely to score higher on the checklist. However, this analysis highlighted many opportunities to strengthen policies by increasing their comprehensiveness and incorporating means to evaluate their effectiveness. So what?: We present a working checklist that can be used for future research and policy development, regarding university alcohol policies and guidelines.